Design and CFD study of a simple wind turbine - Ng, Nicholas Poh Huat (2017)
Due to increasing energy requirements, wind turbine blades have increased in size and flexibility. This results in increasing aeroelastic effects, caused by fluid-structure interactions. Therefore, accurate modelling of these fluid-structure interactions is crucial in the development of larger wind turbines. In this study, a wind turbine blade is designed for operation under optimal conditions, an investigation was conducted on the fluid- structure interactions using computational fluid dynamics (CFD) to calculate the aerodynamic loads caused by fluid flow, which are then applied to a static structural analysis of the turbine blade using finite element analysis (FEA). One-way coupling is used to map the CFD loads to the FEA. The stress distributions and blade deflections are also found to facilitate in future design improvements.